Effect of Osmolarity and Presence of Serum on the Efficiency of Cell Transfection Using Immunoporation - C. Tzavelas; P. Smith; E. Horefti; D. Rickwood (Analytical Cellular Pathology)
Immunoporation is a novel method of cell transfection based upon the use of a new type of beads, Immunofect beads, that can be targeted to make holes in different types of cells depending on the type of bead used. It is known that the efficiency of transfection of cells by some techniques can be affected by the presence of serum and another important factor that appears to affect transfection efficiency and cell viability is the osmolarity of the transfection medium. This report presents studies on the effects of serum and varying osmolarity on the efficiency of transfection using immunoporation. The results clearly indicate that in hypertonic media the presence of serum decreases the efficiency of transfection. In the case of osmolarity, increasing the osmolarity of the immunoporation medium increases the efficiency of transfection but above about 650 mOsm this increasing efficiency is offset by the much lower viability of the cells.